Uric acid profile in apparently healthy people and diabetics - Adam, Ibrahim Khalil; Sheye, Folorunsho Adekunle; Magami, Saminu Musa; Yusuf, Muhammad Bawa (European Journal of Chemistry, 2012)
In recent times, hyperuricaemia has been widely diagnosed in individuals due to changes in lifestyle and as a result of disease conditions that lead to elevated levels of uric acid in the blood. Our present work is on determination of the levels of uric acid in healthy individuals and patients with type 2 diabetes mellitus. Prevalence of hyperuricaemia in relation to age, gender and disease condition was monitored. The results indicated that, levels of uric acid are much higher in subjects that have a combined case of hyperuricaemia and type 2 diabetes mellitus.